A STUDY ON PRE-SERVICE TEACHERS’ PERSPECTIVES OF THE USE OF VISUAL AIDS TO TEACH VOCABULARY TO ELEMENTARY STUDENTS (Trường Đại học Ngoại ngữ, 2025)
This study aimed to investigate the perspectives held by pre-service teachers regarding the use of visual aids in teaching vocabulary to young learners. The study involved 16 pre-service teachers who had recently completed their internships at three primary schools in Danang. The research design used a qualitative and quatitative approach, and data was collected through a questionnaire and interviews. The questionnaire consisted of three parts: general information, sources of visual aids used during the internship, and perspectives on the use of visual aids to teach vocabulary to elementary students. The interviews aimed to obtain a deeper understanding of the participants' responses and to explore their experiences and opinions further.